2018
DOI: 10.1016/j.neunet.2018.04.003
|View full text |Cite
|
Sign up to set email alerts
|

Effect of dilution in asymmetric recurrent neural networks

Abstract: We study with numerical simulation the possible limit behaviors of synchronous discrete-time deterministic recurrent neural networks composed of N binary neurons as a function of a network's level of dilution and asymmetry. The network dilution measures the fraction of neuron couples that are connected, and the network asymmetry measures to what extent the underlying connectivity matrix is asymmetric. For each given neural network, we study the dynamical evolution of all the different initial conditions, thus … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
32
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 29 publications
(36 citation statements)
references
References 37 publications
(58 reference statements)
4
32
0
Order By: Relevance
“…Similar values of the dilution are also found in monkey and mouse visual cortex [19,20], and in human cortex [21]: the reason for which evolution selected asymmetric and diluted connectivity for these areas is still today an open question, which has been so far nearly unexplored [22][23][24]. In our previous research [25], we found that a discrete-time RNN with McCulloch-Pitts neurons possess two network conditions with optimal memory storage, a completely connected and symmetric condition and a diluted asymmetric condition. Furthermore, we show that the optimal RNN condition of dilution and asymmetry corresponds to the dilution and asymmetry values found in the hippocampus and the neocortex.…”
Section: Introductionsupporting
confidence: 75%
See 4 more Smart Citations
“…Similar values of the dilution are also found in monkey and mouse visual cortex [19,20], and in human cortex [21]: the reason for which evolution selected asymmetric and diluted connectivity for these areas is still today an open question, which has been so far nearly unexplored [22][23][24]. In our previous research [25], we found that a discrete-time RNN with McCulloch-Pitts neurons possess two network conditions with optimal memory storage, a completely connected and symmetric condition and a diluted asymmetric condition. Furthermore, we show that the optimal RNN condition of dilution and asymmetry corresponds to the dilution and asymmetry values found in the hippocampus and the neocortex.…”
Section: Introductionsupporting
confidence: 75%
“…This approach allows the direct comparison of the network properties given different symmetry ε and dilution ρ. Until [25], only completely connected McCulloch-Pitts discrete-time recurrent neural networks were considered, thus only networks that shared synaptic connection between all neurons were considered. Clearly, the assumption that any pair of neurons are connected by a synapse is not realistic if we consider brain regions with several neurons, because there would not be sufficient space for all the required connections.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations